Heavy metal whole-cell biosensors using eukaryotic microorganisms: an updated critical review - Gutiérrez, Juan C.; Amaro, Francisco; Martín-González, Ana (Frontiers in Microbiology, 2015)
This review analyzes the advantages and disadvantages of using eukaryotic microorganisms to design whole-cell biosensors (WCBs) for monitoring environmental heavy metal pollution in soil or aquatic habitats. Basic considerations for designing a eukaryotic WCB are also shown. A comparative analysis of the promoter genes used to design WCBs is carried out, and the sensitivity and reproducibility of the main reporter genes used is also reviewed. Three main eukaryotic taxonomic groups are considered: yeasts, microalgae, and ciliated protozoa. Models that have been widely analyzed as potential WCBs are the Saccharomyces cerevisiae model among yeasts, the Tetrahymena thermophila model for ciliates and Chlamydomonas model for microalgae. The advantages and disadvantages of each microbial group are discussed, and a ranking of sensitivity to the same type of metal pollutant from reported eukaryotic WCBs is also shown. General conclusions and possible future developments of eukaryotic WCBs are reported.